Influence of psychosocial factors on attitude in learning English as a second language among rural school students - Zulkefly Balan, Farah (2017)
Students’ attitudes towards learning English as a second language is not a new issue. A lot of research have been done pertaining the factors leading to these attitudes. However, very little is known about how these factors actually affect the students’ attitudes through the lens of not only the students but also their parents, teachers, as well as the educational authorities. Using the social perspectives based on two theories (i.e., Spolsky’s (1989) Model of Second Language Learning and Gardner’s (1985) Second Language Acquisition Theory) as the research framework, this study examines Malaysia students’ attitudes towards learning English as a second language in one rural school in the country, involving 6 students from 3 different classes. Three questions were formulated to guide this study, namely: (i) What are rural secondary school students’ attitudes towards learning the English language?; (ii) What and how are the social and psychological factors influence rural secondary school students’ attitude towards learning the English language?; and (iii) How can positive attitudes be fostered for rural school students to learn the English language?